Consumer acceptance of autonomous delivery robots for last-mile delivery: Technological and health perspectives - Yuen, Kum Fai; Cai, Lanhui; Lim, Yong Guang; Wang, Xueqin (Frontiers in Psychology, 2022)
The unprecedented outbreak of the novel coronavirus has led to a great shift towards online retailing and accelerated the need for contactless delivery. This study investigates how technological and health belief factors influence consumer acceptance of autonomous delivery robots. Anchored in four behavioural theories (i.e. technology acceptance model, health belief model, perceived value theory and trust theory), a synthesised model is developed. A total of 500 valid responses were collected through an online questionnaire in Singapore, and structural equation modelling was conducted to examine the responses. The results revealed that perceived ease of use, perceived usefulness, perceived susceptibility, perceived severity, self-efficacy and cues to action have a positive and significant influence on consumers’ perceptions of the value of autonomous delivery robots. The total effect analysis also showed that perceived value strongly affects consumer acceptance of autonomous delivery robots. Academically, this study introduces both technological and health belief factors to explain consumer acceptance of autonomous delivery robots. It also provides recommendations for policymakers and autonomous delivery robot developers on policy formulation, public communication, product design and infrastructure development.